2021
DOI: 10.1038/s41598-021-91099-1
|View full text |Cite
|
Sign up to set email alerts
|

Liver stiffness regression after sustained virological response by direct-acting antivirals reduces the risk of outcomes

Abstract: The role of liver stiffness measurement (LSM) after sustained virological response (SVR) in HCV patients treated by direct-acting antivirals (DAAs) remains unclear. We aimed to evaluate LSM regression value after SVR and to identify risk factors associated with liver related complications (LRC) or death. This retrospective study analyzed patients with LSM ≥ 10 kPa with LSM by transient elastography pre-DAAs and post-SVR. Patients with previous hepatic decompensation were excluded. Medical records were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Given the above and the multitude of barriers reported in our survey preventing HD-dependent patients from receiving AVT, many individuals may be left untreated without accurate liver fibrosis assessment, despite continued HCV-related abnormalities accumulation. Importantly, fibrosis may serve as a predictor of decompensation or of HCC in patients with CHC, which is why it is important to monitor liver stiffness as recommended by KDIGO [ 11 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the above and the multitude of barriers reported in our survey preventing HD-dependent patients from receiving AVT, many individuals may be left untreated without accurate liver fibrosis assessment, despite continued HCV-related abnormalities accumulation. Importantly, fibrosis may serve as a predictor of decompensation or of HCC in patients with CHC, which is why it is important to monitor liver stiffness as recommended by KDIGO [ 11 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved through the evaluation of fibrosis. It has been documented that liver fibrosis can be utilized for the prognostication of adverse outcomes, patient mortality and as a predictor of decompensation or hepatocellular carcinoma (HCC) occurrence [ 16 , 17 ]. It has also been reflected in the most recent Kidney Disease: Improving Global Outcomes (KDIGO) Work Group guidelines which recommend that all patients with chronic kidney disease (CKD) and CHC be evaluated for fibrosis using noninvasive biomarkers, such as fibrosis-4 (FIB-4), aspartate transaminase-to-platelet ratio index (APRI), or transient elastography [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the significant regression of LSM after treatment of HCV infection with DAAs[ 37 ]. However, it is still debatable whether the decrease of LSM and post-DAA HCV eradication are due to the suppression of viral necro-inflammatory activity or regression of liver fibrosis[ 38 ]. It is recommended that assessing the fibrosis stage after therapy using non-invasive tools should not be endorsed as they are unreliable in this setting[ 29 ].…”
Section: Evaluation Of Severity Of Liver Disorders Before and After T...mentioning
confidence: 99%
“…The proper interpretation of LSM in patients after SVR remains unclear. Many studies have shown a substantial reduction in LSM following SVR in HCV patients treated with DAAs[ 50 - 52 ]. It's still unclear if the drop in LSM after HCV eradication is due to HCV's necro-inflammatory activity being suppressed and changes in hepatic inflammation, rather than the regression of liver fibrosis.…”
Section: Fibrosis Regression Following Hcv Treatment: Does Fibrosis R...mentioning
confidence: 99%